Humanisme Enlightenment: Analisis Strukturalisme Dinamik terhadap Novel Und Friede Auf Erden! Karya Karl May - , LEYGA AINI PRIMA MADUSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Humanism, as one of a movement in philosophy is a study that respecting human, humanity and its values. This research focuses on human values within the scope of the enlightenment era that contains the values of equality, justice and human freedom, unlike the Rennaissance humanism that carries secular humanism which is emphasizing on the separation of the individual values from religion, nor the Romantic humanism that leads to liberal humanism and puts human freedom above everything else. Humanistic discourses can be traced in one of the products of human thought that is literature. Literature as a product of human thought using language as a medium and cointaining imaginary elements, has a communicative function in human society. That means that literary work is a communication tool to deliver messages from the author to the reader. This research is using one of the works of Karl May Und Freide auf Erden! (And Peace on Earth!) as the material object. The research was conducted with the dynamic structuralism theory, developed by Jan Mukarovsky. The theory of dynamic structuralism was applied to reveal the values of humanity contained within the novel UFaE!, not only by understanding the structure of the text, but also by observing the semiotic signs contained in the elements of the novel, so the secondary meaning can also be revealed, and that is the aesthetic value of the literary work. The aesthetic value concerning religious tolerance points out that basically there is only one God